(untitled) (International Journal of Engineering and Computer Science, 2014)
The Web can be defined as a depot of varied range of information present in the form of millions of websites dispersed around us. Often users find it difficult to locate the appropriate information fulfilling their needs with the abundant number of websites in the Web. Hence multiple research work have been conducted in the field of Web Mining so as to present any information matching the user’s needs. The need to fetch the navigation pattern for the website helps in aiding the owners business.